The Role of Influencer Marketing on Tiktok in Shaping Online Shopping Trends: Contribution to Accelerating the Development of Indonesia's Digital Economy - Dwi Winahyo Sutrisna (Eduvest - Journal of Universal Studies, 2026)
The need for innovative and adaptive approaches has become increasingly urgent in the wake of turbulence in the post-global economy following the COVID-19 pandemic, geopolitical instability caused by regional conflicts, monetary policies contributing to the weakening of the United States dollar, and mounting pressures related to environmental and sustainability issues. This study explores the role of influencer marketing on the TikTok platform in shaping online shopping trends as part of efforts to accelerate Indonesia’s digital economy. Amid global economic uncertainty, geopolitical instability, and the weakening of the U.S. dollar, Indonesia requires innovative strategies to strengthen its domestic economy. TikTok, as a social media platform with extensive reach in Indonesia, has become a catalyst for transforming consumer behavior and accelerating e-commerce growth. This research employs a qualitative approach using content analysis and case studies involving 50 Indonesian TikTok influencers. The findings indicate that influencer marketing on TikTok has significantly boosted e-commerce transactions, with a 67% increase recorded during the 2023–2024 period. Furthermore, this phenomenon fosters an inclusive digital economy ecosystem and empowers local MSMEs to compete effectively in the global market.